Smooth Pursuit in Elderly Adults Studied With Apparent Motion. (August 2015) - Bozhkova, Valentina P.; Surovicheva, Nadezhda S.; Nikolaev, Dmitry P.; Nikolaev, Ilya P.; Bolshakov, Andrey S.
The variability of smooth pursuit eye movements was studied in a group of healthy subjects for horizontal apparent motion by a method that does not require direct measurements of eye movements. It was found that the individual smooth pursuit efficiencies for binocular perception in group of healthy elderly subjects (mean age 61 years) as well as in the group of healthy young adults were distinctly differentiated. Furthermore, we have not detected any age-related decrease in the fraction of subjects showing high smooth pursuit efficiencies. This fact demonstrates that the human oculomotor system is relatively resistant to the effects of aging. At the same time, an appreciable increase of percentage of persons with directional asymmetry of smooth pursuit has been found among elderly adults. A higher smooth pursuit efficiency was noticed reliably more often in the direction from left to right rather than in the opposite direction. Subject eye movements were recorded with i-View XTM Hi-Speed 1250 eye tracking system (SMI Inc.). These records confirmed that the smooth pursuit accuracy of older adults is less than that of young persons, at least in some directions of tracking.